Role of p62 in the suppression of inflammatory cytokine production by adiponectin in macrophages: Involvement of autophagy and p21/Nrf2 axis - Nirmala Tilija Pun (Nature Portfolio, 2017)
Abstract Adiponectin possesses potent anti-inflammatory properties. p62, an adaptor protein composed of multi-functional domain, is known to play a role in controlling inflammatory responses. In the present study, we examined the role of p62 in suppressing inflammatory cytokines produced by globular adiponectin (gAcrp) and the potential underlying mechanisms in macrophages. We demonstrated that gAcrp significantly increased p62 expression. Knockdown of p62 abrogated the suppressive effects of gAcrp on LPS-stimulated TNF-α and IL-1β expression and TRAF6/p38 MAPK pathway, indicating that p62 signaling is critical for suppressing inflammatory cytokines production by gAcrp. We next examined the role of p62 in gAcrp-induced autophagy activation, because autophagy has been shown to play a pivotal role in suppressing TNF-α. Herein, we observed that gene silencing of p62 prevented gAcrp-induced increases in autophagy-related genes and autophagosome formation. In addition, we found that Nrf2 knockdown prevented gAcrp-induced p62 expression, and p21 knockdown prevented Nrf2 induction, suggesting the role of p21/Nrf2 axis in gAcrp-induced p62 expression. Taken together, these findings imply that p62 signaling plays a crucial role in suppressing inflammatory cytokine production by globular adiponectin in macrophages, at least in part, through autophagy induction. Furthermore, the p21/Nrf2 signaling cascade contributes to p62 induction by globular adiponectin.